2020
DOI: 10.3390/genes11121487
|View full text |Cite
|
Sign up to set email alerts
|

RNAflow: An Effective and Simple RNA-Seq Differential Gene Expression Pipeline Using Nextflow

Abstract: RNA-Seq enables the identification and quantification of RNA molecules, often with the aim of detecting differentially expressed genes (DEGs). Although RNA-Seq evolved into a standard technique, there is no universal gold standard for these data’s computational analysis. On top of that, previous studies proved the irreproducibility of RNA-Seq studies. Here, we present a portable, scalable, and parallelizable Nextflow RNA-Seq pipeline to detect DEGs, which assures a high level of reproducibility. The pipeline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Degradation of RNA has been shown to impact this procedure and subsequent library preparation; [ 47 ] however, RNA quality numbers (RQN) of sequenced samples were within the recommended range (data not shown). Following other studies in which the same phenomenon was reported, including studies using IC‐BEVS, [ 23,48–50 ] reads mapped to rRNA were removed computationally to avoid its interference with differential expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of RNA has been shown to impact this procedure and subsequent library preparation; [ 47 ] however, RNA quality numbers (RQN) of sequenced samples were within the recommended range (data not shown). Following other studies in which the same phenomenon was reported, including studies using IC‐BEVS, [ 23,48–50 ] reads mapped to rRNA were removed computationally to avoid its interference with differential expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The RNA ow differential gene expression pipeline v1.1.0 [24] was used for transcriptome analysis. This includes read quality control, count normalization, reference-based mapping, gene quanti cation, differential expression, and visualization.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify gene expression levels in the RNA-seq data, we used the nf-core/rnaseq pipeline. This pipeline is an open-source, community-driven pipeline for the analysis of RNA-seq data and is designed to be both reproducible and scalable (Lataretu and Hölzer, 2020). It includes a range of quality control checks, mapping of reads to a reference genome, and quantification of gene expression levels using count-based methods such as featureCounts.…”
Section: Rna-seq Read Mappingmentioning
confidence: 99%